Influenza A virus isolation, culture and identification - Eisfeld, Amie J; Neumann, Gabriele; Kawaoka, Yoshihiro (Nature protocols, 2014)
This protocol describes how to process samples potentially containing influenza A virus (IAV), amplify the samples in chicken eggs or mammalian cells and identify whether and which IAV is present. Influenza A viruses (IAVs) cause epidemics and pandemics that result in considerable financial burden and loss of human life. To manage annual IAV epidemics and prepare for future pandemics, an improved understanding of how IAVs emerge, transmit, cause disease and acquire pandemic potential is urgently needed. Fundamental techniques essential for procuring such knowledge are IAV isolation and culture from experimental and surveillance samples. Here we present a detailed protocol for IAV sample collection and processing, amplification in chicken eggs or mammalian cells, and identification from samples containing unknown pathogens. This protocol is robust, and it allows for the generation of virus cultures that can be used for downstream analyses. Once experimental or surveillance samples are obtained, virus cultures can be generated and the presence of IAVs can be verified in 3–5 d via reverse-transcription (RT)-PCR or hemagglutination assay. Increased time frames may be required for less experienced laboratory personnel, or when large numbers of samples will be processed.